Pathogenetic Targets of Sea Algae Polysaccharides in Non-Alcoholic Fatty Liver Disease - S. P. Kryzhanovsky; L. G. Guseva; E. Yu. Dobryakov; L. N. Fedyanina; T. S. Zaporozhets (Антибиотики и Химиотерапия)
To date, in vivo and in vitro experiments, as well as clinical studies, have identiﬁed antihyperlipidemic, anti-inﬂammatory, immunomodulatory, antioxidant, antidiabetic, gastro- and hepatoprotective eﬀects of polysaccharides from various types of algae, which are used for medical purposes as biologically active additives (BAA) to food, due to their biocompatibility, low toxicity (most of them are completely nontoxic), as well as the ability to act simultaneously on many pathogenetic targets in somatic and infectious diseases. The review presents the latest materials on the prospects of using marine polysaccharides for the prevention and treatment of non-alcoholic fatty liver disease (NAFLD), the most common chronic disease of this organ. Experimental data on the ability of algae polysaccharides to modulate insulin sensitivity, increase the activity of β-oxidation of fatty acids, reducing the lipid load in the liver, are summarized. The antioxidant and anti-inﬂammatory potencies of polysaccharides, as well as their eﬀect on the intestinal microbiota, play a signiﬁcant role in protecting the liver in NAFLD. Further studies are required to clarify the mechanism of action of brown algae polysaccharides on liver cells, to determine the composition and clinical availability of these compounds in the form of algae products, nutritional supplements, and regulated therapeutics.